Dispersive Liquid–Liquid Chelate Microextraction of Rare Earth Elements: Optimization and Greenness Evaluation - Milica Delić; Mirjana Ristić; Maja Đolić; Aleksandra Perić-Grujić; Antonije Onjia (Metals)
An ultrasound-assisted dispersive liquid–liquid microextraction (DLLME) method was developed to concentrate and quantify rare earth elements (REEs) (Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu) in acidic aqueous solutions. Tetrachloroethylene (PCE) was used as the diluent, di-(2-ethyl hexyl) phosphoric acid (D2EHPA) as the extracting agent, and acetone as the dispersant solvent. The method was optimized at pH = 2.3, T = 25 °C, and VS = 400 µL of a PCE ÷ D2EHPA mixture (10 ÷ 1) using the response surface methodology (RSM) with a Box–Behnken design. Under optimal conditions, the method proved efficient for the DLLME of most REEs (Y, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu), where the achieved recoveries were in the range of 61–109%, while relative standard deviations were in the range 11–28%. The proposed method was applied to recover REEs from real coal ash leachate samples. A greenness evaluation using the Green Analytical Procedure Index (GAPI), Analytical GREEnness (AGREE), and Analytical Eco-Scale (AES) methodologies revealed acceptable metric scores of 74, 0.61, and 26.6–79.8, respectively.